Antioxidant Action and In Vivo Anti-Inflammatory and Antinociceptive Activities of Myrciaria floribunda Fruit Peels: Possible Involvement of Opioidergic System. (27th April 2020) - Santos, Izabelly Bianca da Silva; Santos dos Santos, Bruno; Oliveira, João Ricardhis Saturnino de; Costa, Wêndeo Kennedy; Zagmignan, Adrielle; da Silva, Luís Cláudio Nascimento; Ferreira, Magda Rhayanny Assunção; Lermen, Vilmar Luiz; Lermen, Maria Silvanete Benedito de Sousa; da Silva, Alexandre Gomes; Ximenes, Rafael Matos; Soares, Luiz Alberto Lira; et al.
Abstract : This work evaluated the antioxidant properties and in vivo antinociceptive and anti-inflammatory effects of extracts obtained from fruit peels of Myrciaria floribunda (H. West ex Willd.) O. Berg (Myrtaceae). This plant is popularly known in Brazil as Cambuí or camboim . Different extracts were submitted to comparative analysis to determine the content of selected phytochemical classes (levels of total phenols, flavonoids, and monomeric anthocyanins) and the in vitro antioxidant potentials. The extract with higher potential was selected for in vivo evaluation of its antinociceptive and anti-inflammatory action. Finally, the chemical characterization of this extract was performed by high-performance liquid chromatography (HPLC). MfAE (extract obtained using acetone as solvent) showed the higher levels of phenols (296 mg GAE/g) and anthocyanins contents (35.65 mg Cy-3-glcE/g) that were associated with higher antioxidant activity. MfAE also exhibited in vivo anti-inflammatory and analgesic propertiers. This fraction inhibited the inflammatory and neurogenic phases of pain, and this effect was reversed by naloxone (suggesting the involvement of opioidergic system). MfAE reduced the abdominal contortions induced by acetic acid. The HPLC analysis revealed the presence of gallic acid (and its derivatives) and ellagic acid. Taken together, these data support the use of M. floribunda fruit peels for development of functional foods and nutraceutics.